ANALISIS TINGKAT PELANGGARAN LALU LINTAS DI WILAYAH POLRES GROBOGAN MENGGUNAKAN METODE CLUSTERING K-MEANS - Niken Silvia Anggraini; MY Teguh Sulistyono (LPPM Universitas Abdurrab, 2026)
The increasing number of vehicle users in Grobogan Regency has resulted in a high number of traffic violations that have the potential to cause accidents and traffic congestion. This study aims to analyze the level of traffic violations using the K-Means clustering method. The data used is primary data from the Grobogan Police Traffic Unit for the 2020-2024 period with a total of 38,318 violation cases. The research process consists of data preprocessing which includes number extraction, text transformation, and normalization, determining the number of clusters using the Elbow method, and a clustering evaluation process using the Davies-Bouldin Index (DBI). The results of the analysis show that the data on the level of traffic violations can be grouped into minor violations of more than 3,000 cases, which include violations of not wearing a helmet and violating traffic signs, moderate violations of approximately 5,000 cases, which include violations of not carrying a driver's license or vehicle registration, and severe violations of approximately 1,000 cases, which involve large vehicles. Evaluation of the quality of clustering using the Davies-Bouldin Index (DBI) shows that the arrangement with three groups (k = 3) provides the smallest DBI value, namely 0.486770. This figure indicates that the formation of three groups is the best arrangement, so that the results of the grouping divided into categories of minor, moderate, and severe violations have a fairly good quality of grouping. These results are expected to be a reference for the Regional Police and local governments in developing more effective law enforcement strategies and traffic safety policies.